Work status as depicted by the Holy Quran - Zahedi, Abdullah (Journal of Islamic Sciences, 2019)
This study deals with the status of work as depicted in the Holy Quran, based on the descriptive method. The aim was to define the work, the word "work" in the Holy Quran, the work called for by the Qur’an, the honor of its owner, the imposition of work, Agriculture, trade and industry in addition to mastering the work that Islam has urged and the aim of the work is to address poverty in Islam for the individual state. The study has concluded that the word "work" has been mentioned in the Quran more than once and in most cases comes some faith, The Qur’an calls for all action Fit by the individual and society, and its suitable world and religion, Islam has called for men and women to work and did not differentiate between them; except where dispersed nature between them. The study indicates the importance of perfection in the performance of work, and indicate the purpose of production, and its goal, and refers to the treatment of Islam to the problem of poverty.